THE CREMATION OF CORPSES IN THE CURRENT CANON CODIFICATION AND ITS PASTORALITY: STUDY FROM § 3 OF CANON 1176 OF THE 1983 CODE OF CANON LAW - Chagas Ramos, Rawy (Revista Gênero e Interdisciplinaridade, 2024)
This article, The Cremation of Corpses in the Current Canonical Codification and Its Pastoral Care: A Study Based on § 3 of Canon 1176 of the 1983 Code of Canon Law, derived from a master’s thesis in Canon Law, is a detailed study on the acceptance of cremation within the context of the Catholic Church, marking a significant evolution from traditional burial norms. Employing a bibliographic research methodology, the article analyzes a wide range of sources, including books, scientific articles, and official Church documents, to outline a historical, theological, and legal panorama on the subject. The research highlights the transformation in the perception of death and funeral practices over time, examining the development of ecclesiastical norms from the initial prohibition of cremation in the 1917 Code to its conditional acceptance in subsequent legislations, culminating in the 2016 instruction Ad resurgendum cum Christo. This evolution reflects an adaptive response to social and cultural changes, maintaining consistency with the principles of the Christian faith. The historical and legal understanding of cremation in light of Vatican II provides a clearer and truer comprehension of funerals and cremation in the canonical and pastoral context of the Church. Finally, the article emphasizes the importance of pastoral care in funerals, highlighting cremation as a viable option that, while not preferred, is permitted as long as it does not oppose the doctrine of resurrection, reiterating the message of hope in eternal life.